Tropical liver abscess. - Yeoh, K. G. (BMJ Group, 1997)
Forty-one consecutive cases of liver abscesses seen at the National University Hospital, Singapore from 1988 to 1994 were reviewed. Twenty-seven cases (65%) were pyogenic, six (15%) amoebic, two (5%) tuberculous and six (15%) indeterminate. The predominance of pyogenic abscesses is in marked contrast to previous studies from the region a decade ago in which amoebic abscesses were the commonest type. The commonest pathogen causing pyogenic abscess was Klebsiella pneumoniae. Two cases were due to Mycobacterium tuberculosis, and this organism needs to be actively looked for in smears and cultures of aspirated material. As the majority of organisms isolated were resistant to ampicillin, empirical antibiotic treatment for suspected pyogenic abscess should include gentamicin or a cephalosporin. Percutaneous needle aspiration of the abscess was performed for 85% of pyogenic abscesses and surgery was necessary in only two cases because of complications. We found that percutaneous aspiration of liver abscess is helpful to confirm the diagnosis, provides a better bacteriological culture yield, gives a good outcome, and may uncover clinically unsuspected conditions like malignancy and tuberculoma which may mimic the presentation of liver abscesses. We recommend routine cytological examination of aspirated abscess material as well as stains and cultures for acid-fast bacilli.